Substituting fish meal with castor meal in diets of hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂): Effects on growth performance, immune response, antioxidant and digestive enzyme activities, gut morphology, and inflammatory-related gene expression. Issue 131 (December 2022) - Amoah, Kwaku; Yan, Xiaobo; Liu, Hao; Pan, Simiao; Li, Tao; Suo, Xiangxiang; Tan, Beiping; Zhang, Shuang; Huang, Weibin; Xie, Mingsheng; Yang, Shipei; Zhang, Haitao; et al.
Abstract: The present study was conducted to investigate the effects of replacing fishmeal (FM) with castormeal (CM) on the growth performance, immune response, antioxidant and digestive enzyme activities, intestinal morphology, and expression of inflammatory-related genes in juvenile hybrid grouper ( Epinephelus fuscoguttatus ♀ × E . lanceolatus ♂). Six iso-nitrogenous (50% crude protein) and iso-lipidic (10% crude lipid) diets were formulated; namely, a reference diet (FM) containing 50% FM and five experimental diets (4% (CM4), 8% (CM8), 12% (CM12), 16% (CM16), and 20% (CM20)) in which FM protein was substituted with CM at varying levels to feed fish (initial weight: 9.12 ± 0.01 g) for 8 weeks. The results showed that the final weight, weight gain rate, and specific growth rate were highest in the FM, CM4, and CM8 groups, whereas the feed conversion ratio, hepatosomatic and viscerosomatic indexes were significantly enhanced in the CM4 group in comparison to the others. The CM4 and CM12 groups were observed to show the highest intestinal length index values compared to the other groups, with the CM20 revealing the worst growth performance. The serum total protein content first increased ( P < 0.05) in the CM4 group and decreased ( P < 0.05) afterward. Nonetheless, a decreasing significant ( P < 0.05) cholesterol and triglyceride contents were witnessed with the increasing replacement of FM with CM. Compared to the control group, a significant increase ( P < 0.05) in the activities of serum and liver immunoglobulin-M, superoxide dismutase, glutathione peroxidase, total antioxidant capacity, and complement-3 (except serum activity for CM12 group); liver lysozyme; intestinal amylase, and lipase, was witnessed in the CM groups. However, the serum lysozyme activity was highest ( P < 0.05) in the CM4 group and lowest in the CM20 group. While the least serum malondialdehyde contents were observed in the CM4 group, that of the liver malondialdehyde was least witnessed in the FM, CM4, CM8, CM12, and CM16 groups as compared to the CM20. The intestinal histological examination revealed a significantly decreasing trend for villi height and villi width with increasing replacement levels. However, the muscle thickness, crypt depth, and type II mucus cells first increased upto 4% replacement level and later decreased. The increasing of dietary replacement levels significantly up-regulated pro-inflammatory ( il-1β, tnf-α, myd88, ifn-γ, tlr-22, and il-12p40 ) and down-regulated anti-inflammatory ( il-10, tgf-β, mhc-iiβ ) and anti-bacterial peptide ( epinecidin and hepcidin ) mRNA levels in the intestine. The mRNA levels of il-6 was up-regulated firstly upto 4 and 8% replacement levels, and later down-regulated with increasing replacement. These results suggested that, although higher dietary CM replacement enhances the immune, antioxidant and digestive enzymes, it aggravates intestinal inflammation. Replacing 4 and 8% of FM with CM could enhance the growth performance of fish. Highlights: The effects of Castormeal (CM) on immune responses and gut health of hybrid grouper was evaluated. Results suggest 4% and 8% replacement of fishmeal (FM) with CM could help to improve the growth performance. Higher replacement of CM enhances immune response and antioxidant enzyme activities. Higher replacement of FM with CM induces enteritis in hybrid grouper fish. Replacement of FM with CM causes significant effects on the expression of inflammatory cytokines and antimicrobial peptide genes.